2013
DOI: 10.1161/circulationaha.112.000029
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Unloading the Left Ventricle Before Coronary Reperfusion Reduces Left Ventricular Wall Stress and Myocardial Infarct Size

Abstract: Background-Ischemia/reperfusion injury worsens infarct size, a major determinant of morbidity and mortality after acute myocardial infarction (MI). We tested the hypothesis that reducing left ventricular wall stress with a percutaneous left atrial-to-femoral artery centrifugal bypass system while delaying coronary reperfusion limits myocardial injury in a model of acute MI. Methods and Results-MI was induced by balloon occlusion of the left anterior descending artery in adult male swine. In the MI group (n=4),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 157 publications
(113 citation statements)
references
References 44 publications
4
109
0
Order By: Relevance
“…The redirection of blood from the LA reduces LV preload, LV workload, filling pressures, wall stress, and myocardial oxygen demand. 47,48 The increase in arterial blood pressure and cardiac output supports systemic perfusion. The 19 Fr arterial cannula allows up to 5 L/min of flow whereas the 15 Fr cannula will allow up to 3.5 L/min.…”
Section: Hemodynamic Effectsmentioning
confidence: 99%
“…The redirection of blood from the LA reduces LV preload, LV workload, filling pressures, wall stress, and myocardial oxygen demand. 47,48 The increase in arterial blood pressure and cardiac output supports systemic perfusion. The 19 Fr arterial cannula allows up to 5 L/min of flow whereas the 15 Fr cannula will allow up to 3.5 L/min.…”
Section: Hemodynamic Effectsmentioning
confidence: 99%
“…The redirection of blood from the LA reduces LV preload, LV workload, filling pressures, wall stress, and myocardial oxygen demand [47,48]. The increase in arterial blood pressure and cardiac output supports systemic perfusion.…”
Section: Hemodynamic Effectsmentioning
confidence: 99%
“…Ventricular unloading may reduce myocardial infarct size through enhanced hemodynamics, preserved energetics, and activation of cardioprotective mechanisms [48,116]. Despite limited unloading potency, some animal infarct model studies found improved myocyte recovery with IABP use [117,118].…”
Section: Future Directions: Myocyte Protection and Recoverymentioning
confidence: 99%
“…Although some experimental myocardial infarct size studies using intra-aortic balloon counterpulsation (IABP) showed reductions in infarct size, 10 this technique, which primarily reduces afterload, was unsuccessful in reducing myocardial infarct size in humans or in reducing death from cardiogenic shock. 11,12 The reason for the negative clinical trials is unclear, as discussed by Kapur et al 13 Experimental studies with a catheter-mounted axial flow pump (moving blood from LV to aorta) that reduced preload, did reduce infarct size in experimental models. 14 Smalling et al 14 subjected anesthetized dogs to 2 hours of left anterior descending coronary artery occlusion followed by 1 hour of reperfusion and compared the effect of a Hemopump transvalvular axial-flow LV assist device with IABP on LV unloading, coronary collateral blood flow, and reduction of infarct size.…”
Section: Mechanical Unloading For Reducing Infarct Sizementioning
confidence: 99%
“…Kapur et al 13 provide an intriguing study in this issue of Circulation, suggesting that a circulatory support device that reduces LV preload with a left atrial to femoral artery pumping approach decreased LV wall stress and LV stroke work after reperfusion and limited infarct size even when treated animals received an additional 30 minutes of ischemia, during which LV unloading was activated. The benefit of this type of unloading may be secondary to the reduction in oxygen demand, but also intriguing was their observation that phosphorylation of reperfusion injury salvage kinase pathway proteins (pERK and pAkt) was increased in samples of the LV obtained from the noninfarct zone (but not the infarct zone).…”
Section: The Present Studymentioning
confidence: 99%